Active and Healthy Aging After COVID-19 Pandemic in Portugal and Other European Countries: Time to Rethink Strategies and Foster Action - Costa, Andreia; Câmara, Gisele; Arriaga, Miguel Telo de; Nogueira, Paulo; Miguel, José Pereira (Frontiers in Public Health, 2021)
The population aging in Europe imposes challenges to societies that require adaptations and responses at various levels to minimize impacts and figuring out opportunities. Portugal has been committed to the World Health Organization and European Union's values and policy frameworks concerning active and healthy aging. In 2017, an inter-ministerial working group developed the National Strategy for Active and Healthy Aging. In the face of the COVID-19 pandemic that exposed the vulnerabilities of older populations, the launch of the Decade of Healthy Aging 2021–2030 and its baseline report and the 2018 Active Aging Index Analytical Report may constitute an opportunity to strategically think about the aging of the population as a national purpose in Portugal and in the other European countries that face similar challenges.